Bone marrow stromal cells from multiple myeloma patients uniquely induce bortezomib resistant NF-κB activity in myeloma cells - Markovina, Stephanie (BioMed Central, 2010)
BACKGROUND: Components of the microenvironment such as bone marrow stromal cells (BMSCs) are well known to support multiple myeloma (MM) disease progression and resistance to chemotherapy including the proteasome inhibitor bortezomib. However, functional distinctions between BMSCs in MM patients and those in disease-free marrow are not completely understood. We and other investigators have recently reported that NF-κB activity in primary MM cells is largely resistant to the proteasome inhibitor bortezomib, and that further enhancement of NF-κB by BMSCs is similarly resistant to bortezomib and may mediate resistance to this therapy. The mediating factor(s) of this bortezomib-resistant NF-κB activity is induced by BMSCs is not currently understood. RESULTS: Here we report that BMSCs specifically derived from MM patients are capable of further activating bortezomib-resistant NF-κB activity in MM cells. This induced activity is mediated by soluble proteinaceous factors secreted by MM BMSCs. Among the multiple factors evaluated, interleukin-8 was secreted by BMSCs from MM patients at significantly higher levels compared to those from non-MM sources, and we found that IL-8 contributes to BMSC-induced NF-κB activity. CONCLUSIONS: BMSCs from MM patients uniquely enhance constitutive NF-κB activity in MM cells via a proteinaceous secreted factor in part in conjunction with IL-8. Since NF-κB is known to potentiate MM cell survival and confer resistance to drugs including bortezomib, further identification of the NF-κB activating factors produced specifically by MM-derived BMSCs may provide a novel biomarker and/or drug target for the treatment of this commonly fatal disease.